Adherence to a Telephone-Supported Depression Self-Care Intervention for Adults With Chronic Physical Illnesses. (23rd February 2015) - Simco, Russell; McCusker, Jane; Sewitch, Maida; Cole, Martin G.; Yaffe, Mark; Lavoie, Kim L.; Sussman, Tamara; Strumpf, Erin; Ciampi, Antonio; Belzile, Eric
We assessed adherence to and predictors of two components of a telephone-supported self-care intervention for depression among primary care adults aged 40 and above with chronic physical illnesses and comorbid depressive symptoms. Participants received a "toolkit" containing six self-care tools. Trained lay self-care "coaches" negotiated a contact schedule of up to weekly contacts. Study outcomes were levels of completion of the self-care tool and the coach contacts at the 2-month follow-up. Coaches reported the number of completed contacts. In all, 57 of 63 participants completed the 2-month follow-up. Of these, 67% completed at least 1 tool; the mean number of coach contacts was 5.7 ( SD = 2.4) of a possible 9 contacts (63% adherence). Higher disease comorbidity and lower initial depression severity independently predicted better tool adherence. Findings suggest that people with chronic physical illnesses can achieve acceptable levels of adherence to a depression self-care intervention similar to those reported for other populations.